2009
DOI: 10.1158/0008-5472.can-08-3820
|View full text |Cite
|
Sign up to set email alerts
|

Computational Identification of a p38SAPK-Regulated Transcription Factor Network Required for Tumor Cell Quiescence

Abstract: The stress-activated kinase p38 plays key roles in tumor suppression and induction of tumor cell dormancy. However, the mechanisms behind these functions remain poorly understood. Using computational tools, we identified a transcription factor (TF) network regulated by p38A/B and required for human squamous carcinoma cell quiescence in vivo. We found that p38 transcriptionally regulates a core network of 46 genes that includes 16 TFs. Activation of p38 induced the expression of the TFs p53 and BHLHB3, while in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
203
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(205 citation statements)
references
References 42 publications
(72 reference statements)
2
203
0
Order By: Relevance
“…However, these results should be interpreted with caution as decidualising endometrial cells acquire a highly secretory phenotype, suggesting that miRNAs may be produced primarily for export. It should also be observed that several miRNA species can regulate ER and PR expression (Pandey & Picard 2010), and the experimentally validated miRNAs that can control ER expression include miR-18ab, miR-19, miR-22, miR-26ab/1297, miR-181, miR-206 and miR-222/221 (Adam et al 2009, Castellano et al 2009, Pandey & Picard 2009, Di Leva et al 2010. PR expression has also been found to be modulated by miR-181 and miR-26ab/1297 (Castellano et al 2009).…”
Section: Mirnas and Endometrial Functionmentioning
confidence: 99%
“…However, these results should be interpreted with caution as decidualising endometrial cells acquire a highly secretory phenotype, suggesting that miRNAs may be produced primarily for export. It should also be observed that several miRNA species can regulate ER and PR expression (Pandey & Picard 2010), and the experimentally validated miRNAs that can control ER expression include miR-18ab, miR-19, miR-22, miR-26ab/1297, miR-181, miR-206 and miR-222/221 (Adam et al 2009, Castellano et al 2009, Pandey & Picard 2009, Di Leva et al 2010. PR expression has also been found to be modulated by miR-181 and miR-26ab/1297 (Castellano et al 2009).…”
Section: Mirnas and Endometrial Functionmentioning
confidence: 99%
“…In this study we have been able to observe FOXM1 to act downstream from RAS-MKK3-p38 and confer invasion and anchorageindependent growth signals. Recently published data demonstrate furthermore, that upregulation of FOXM1 prevents apoptosis and senescence (Park et al, 2009) and may even be downregulated upon induction of dormancy through p38 (Adam et al, 2009). Thus, FOXM1 may serve as a therapeutic target to eliminate those effects of the p38 pathway that support the malignant phenotype, without affecting possible induc- Figure 6 siRNA-mediated knockdown of FoxM1leads to downregulation of p38-dependent invasion, which can be restored by overexpression of FoxM1.…”
Section: Foxm1 Is a Downstream Target Of Ras-mkk3-p38mentioning
confidence: 99%
“…40 Previous studies examining transcription factor profile analysis revealed that c-JUN/AP-1 is negatively regulated by p38 phosphorylation. 24,41 In fact, it was found to be reduced in dormant D-HEp3 cells 25 and also in the ERp29-overexpressing MDA-MB-231 cell model. 6 The ERp29-mediated downregulation of basal eIF2a could be due to the inhibition of c-JUN by activation of p38.…”
Section: Discussionmentioning
confidence: 95%
“…18,24 The mechanistic link between ER stress and tumor cell growth arrest through p38 activation suggests an important role of p38-regulated networks in modulating tumor cell quiescence, survival and apoptosis. 18,24,25 Hence, cells may coordinate growth arrest and survival signals by activating ER stress, leading to resistance to stress-induced death ( Figure 1).…”
mentioning
confidence: 99%